Menjembatani Teori Dan Praktik: Pemberdayaan Mahasiswa Manajemen Melalui Workshop Metodologi Penelitian dan Skill-Building - Arizal Hamizar; Fadli Fendi Malawat; Afdhal Yaman; Muammar Wijayanto Maruapey (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
This study depicts the implementation of community engagement in the form of a research methodology writing workshop in the field of management. The workshop aims to provide an in-depth understanding of quantitative and qualitative research methodologies to participants. An interactive approach is utilized by presenting materials from two expert speakers in the field. The workshop comprises three sessions, with the first session discussing quantitative research methods, the second session addressing qualitative research methods, and the third session involving participants in creating a mini research project using one of the methods. The results indicate that the workshop successfully enhances participants' comprehension and skills in designing, conducting, and analyzing research in the field of management. The workshop offers an opportunity for participants to integrate theory with practice and develop critical and analytical thinking skills. Additionally, the workshop lays a robust foundation for the development of research competence and professionalism among participants in the business and management realm.Keywords: Management, Workshop, Research Methodology.